Weak localization in bilayer graphene with Li-intercalation/desorption. (2nd July 2018) - Endo, Y; Ichinokura, S; Akiyama, R; Takayama, A; Sugawara, K; Nomura, K; Takahashi, T; Hasegawa, S
Abstract: We performed in-situ electrical transport measurements for bilayer graphene grown on SiC(0 0 0 1) substrate, Li-intercalated bilayer graphene, and after that desorbing Li atoms by heating. Bilayer graphene after desorbing intercalated Li atoms showed a higher resistivity and different behavior in magnetoconductance compared to pristine bilayer graphene. We observed the weak localization of carriers at low temperatures in all the three samples and analyzed the experimental results with the extended Hikami–Larkin–Nagaoka equation to investigate the transport properties. The result shows that the magnetoconductance of pristine bilayer graphene is described by the AB stacking structure model and the phase breaking scattering is dominated by the electron–electron scattering. The intra-valley scattering occurs most frequently probably due to dopants in SiC substrate. However, in Li-desorbed graphene, the magnetoconductance can be described by neither AB nor AA-stacking model, suggesting the coexistence of domains with several different stacking structures.